Os bancos brasileiros na internet: um estudo de caso sobre os motivadores para a sua forma de atuação neste ambiente - Ferreira, Carlos Eduardo Coelho (2010)
The research focus is to present an integrated analysis model for the behavior pattern of Brazilian banks in the Internet environment. A single case study was conducted at Banco do Brasil. Most interviews took place at Banco do Brasil’s administrative and technology headquarters in the city of Brasília, DF. An Integrated Analysis Model was presented based in many theories and structures of the organizational studies and information systems fields. Findings show that the studied phenomena can be understood with the simultaneous application of all selected theories, proving the complexity of the study object. Research limitations include the fact that this research was focused on a single case and also that it was not possible to run this research with a bigger sample of organizations. Study originality and contribution relies on proposing the Integrated Analysis Model with analysis structures and theories that help to understand the object of study. Future studies may replicate this research in a bigger number of companies to present a richer analysis.